Zazakî de Ergatîvîte - Kırkan, Ahmet (Muş Alparslan Üniversitesi, 2021)
Ergativite ve bunun cümleler üzerindeki etkisi, diller arasındaki büyük farklardan biridir. Ergativite, Farsça gibi dillerde herhangi bir tesiri kalmamıştır ama Zazacada halen etkisini sürdürmektedir. Lakin Zazaca da tam ergatif bir dil değildir. Zazacada ergativite sadece geçmiş zamanda kalmış olup, bu anlamda Zazaca yarım-ergatif bir dildir. Bu çalışmanın amacı Zazacada ergativiteyi açıklamaktır. Çalışmada bazen Zazaca ve Kurmancca karşılaştırmalı olarak verilmiştir. Zazacada eski dillerde olan arkaik özellikler kalmış ve korunmuştur. Çalışmada ergativite geçişli ve geçişsiz fiil çekimlerine bağlı olarak açıklanacaktır. Bu çalışmada standart Zazaca kullanılmıştır. Çünkü bazı ağızlarda ergativite ortadan kalkmaktadır.

Ergativity and its effect on sentences is one of the big differences between languages. Ergativity has no effect on languages such as Persian, but in Zaza language still continues. However, Zazaki is not a fully ergative language either. In Zaza language, ergativity is only in the past, and in this sense, Zazaki is a semi-ergative language. The aim of this study is to explain the ergativity in Zaza language. In the study, sometimes Zazaki and Kurmanci are given comparatively. In Zaza language, the archaic features of the old languages have remained and preserved. In the study, ergativity will be explained depending on transitive and intransitive verb conjugations. In this study, standard Zaza language is used. Because in some dialects, ergativity disappears.
Ergativity in the Zaza Language
anemon
Keywords: Zazaca; Ergativite; Geçişli Fiil; Geçişsiz Fiil; Absolutif; Ergativity; Zazaki; Transitive Verb; Intransıtıve Verb; Absolutive